Tree-related microhabitats and deadwood dynamics form a diverse and constantly changing mosaic of habitats in boreal old-growth forests. (September 2021) - Martin, Maxence; Fenton, Nicole J.; Morin, Hubert
Graphical abstract: Highlights: Microhabitat and deadwood dynamics in boreal old-growth forests are nonlinear. High variability in habitats, hence in biodiversity, defines old-growth forests. Highest deadwood abundance and diversity is found in true old-growth forests. Peak in microhabitat abundance and diversity may be temporary. Microhabitats are abundant despite small tree size and hardwood species scarcity. Abstract: Tree-related microhabitats (TreM) and deadwood are two forest attributes providing essential resources for biodiversity conservation and ecosystem services. Old-growth forests are generally defined by a high abundance and diversity of TreM and deadwood, but little is known about TreM and deadwood dynamics once the old-growth stage is reached, in particular in the boreal biome. In this context, knowledge on TreM and deadwood dynamics in old-growth forest stands is necessary to better understand how these forests contribute to biodiversity and ecosystem services. The aim of this study is thus to determine how TreM, and deadwood abundance and diversity vary within boreal old-growth forests. To reach this objective, we surveyed TreM and deadwood attributes, as well as structural and abiotic attributes, in 71 boreal old-growth forests situated in Quebec, Canada. We used hierarchical clustering analysis to identify TreM and deadwood abundance and diversity patterns in the studied stands. We identified five clusters of TreM and deadwood characteristics, which corresponded to three stages of old-growth forest succession: canopy break-up (beginning of the old-growth stage), transition old-growth stage (replacement of the first cohort by old-growth cohorts) and true old-growth stage (first cohort all or almost all gone). The peak in TreM richness and diversity was reached at the transition old-growth stage, whereas the peak for deadwood richness and diversity was reached at the true old-growth stage. Overall, true old-growth forests were defined by a combination of moderate to high TreM density and high deadwood volume, but these values significantly varied among stands depending on past secondary disturbances, stand structure and its composition (black spruce [ Picea mariana Mill.] dominated vs mixed black spruce – balsam fir [ Abies balsamea (L.) Mill.]). These results therefore underscore the importance of considering old-growth forests as dynamic rather than static ecosystems, as the composition of tree- and deadwood-related microhabitats in the same old-growth stand may markedly change over time. At landscape scale, these results also imply that the mosaic of habitats present in old-growth forests can vary greatly from one location to another, highlighting the importance of maintaining a diversity of old-growth forest structure and composition.